2010
DOI: 10.1590/s1516-635x2010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular studies of the Brazilian infectious bronchitis virus isolates

Abstract: Avian infectious bronchitis virus (IBV) isolates have been widely characterized by reverse transcription followed by polymerase chain reaction and DNA sequencing. In present study, these techniques were applied to three viral genomic regions comprising the complete and/or a partial S1 segment, S2 and nucleocapsid genes. DNA sequences from viral isolates obtained from 1972 to 1989 and from 2006 to 2008 were compared. High similarity (>90%) was observed among some of the genomic segments, including S1 hypervaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Most of the isolates from this study were identified as belonging to the BR-I genotype (CHACON et al, 2011). This genotype appeared to be the most disseminated and predominant IBV variant causing disease in poultry, because our results and other epidemiological studies detected this genotype in different Brazilian regions (ABREU et al, 2010;FELIPPE et al, 2010) from birds with respiratory, renal, enteric or reproductive signs and mortality. Additionally only the isolate USP 555-6 (detected in tracheal tissue) clustered together with isolates belonging to the BR-II genotype (Figure 2).…”
Section: Ibv Detection and Genotypingsupporting
confidence: 60%
“…Most of the isolates from this study were identified as belonging to the BR-I genotype (CHACON et al, 2011). This genotype appeared to be the most disseminated and predominant IBV variant causing disease in poultry, because our results and other epidemiological studies detected this genotype in different Brazilian regions (ABREU et al, 2010;FELIPPE et al, 2010) from birds with respiratory, renal, enteric or reproductive signs and mortality. Additionally only the isolate USP 555-6 (detected in tracheal tissue) clustered together with isolates belonging to the BR-II genotype (Figure 2).…”
Section: Ibv Detection and Genotypingsupporting
confidence: 60%
“…Phylogenetic analysis using the spike glycoprotein S1 coding region is useful for the differentiation and classification of IBV strains and lineages, and for predicting levels of cross‐protective immunity (Bayry et al., 2005; Valastro et al., 2016). Multiple studies carried out in Latin America have identified IBV as causing disease on poultry farms across the region, in both vaccinated and unvaccinated settings (Abreu et al., 2010; Jackwood, 2012; Villarreal et al., 2010). Further analysis of novel strains identified in Brazil, Argentina and Uruguay revealed distinctive South American lineages.…”
Section: Discussionmentioning
confidence: 99%
“…The scale bar represents the number of nucleotide substitutions per site, and the tree is mid-point rooted for sake of clarity only [Colour figure can be viewed at wileyonlinelibrary.com] Phylogenetic analysis using the spike glycoprotein S1 coding region is useful for the differentiation and classification of IBV strains and lineages, and for predicting levels of cross-protective immunity (Bayry et al, 2005;Valastro et al, 2016). Multiple studies carried out in Latin America have identified IBV as causing disease on poultry farms across the region, in both vaccinated and unvaccinated settings (Abreu et al, 2010;Jackwood, 2012;Villarreal et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation